Preparations of Organoclay Using Cationic Surfactant and Characterization of PVC/ (Bentonite and Organoclay) Composite Prepared via Melt Blending Method - Abdul majeed, Basma A.; Sabar, Dhilal Amer (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Calcium-Montmorillonite (bentonite) [Ca-MMT] has been prepared via cation exchange reaction using benzalkonium chloride [quaternary ammonium] as a surfactant to produce organoclay which is used to prepare polymer composites. Functionalization of this filler surface is very important factor for achieving good interaction between filler and polymer matrix. Basal spacing and functional groups identification of this organoclay were characterized using X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) spectroscopy respectively. The (XRD) results showed that the basal spacing of the treated clay (organoclay) with the benzalkonium chloride increased to 15.17213 0A, this represents an increment of about 77.9% in the basal spacing. FTIR spectra illustrate that benzalkonium chloride compound was successfully intercalated in to clay layers. The results confirm the effectiveness of the synthesis of organoclay with similar characteristics compared to those ones observed in the bentonite. The features were obtained by a simple process and enable interaction with organic compounds (polymers and plastic). PVC/bentonite composite and PVC/organoclay composite were prepared by the melt intercalation method .The results have been analyzed and compared for PVC samples with (3wt%, 7wt% and 12wt %) bentonite and organoclay micro filler .Mechanical properties, thermal properties, flammability and water absorption percentage of prepared samples were tested. Mechanical characteristic such as tensile strength, elongation at break, hardness and impact strength (charpy type) were measured for all samples, where the tensile strength and elongation at break of PVC composites increased with increasing organoclay loading compared with unmodified bentonite. Also, the hardness and impact strength of the composites increase with increase in filler content. Thermal properties of PVC/ (bentonite, organoclay) composites were characterized using Differential Scanning Calorimeter (DSC) and thermal conductivity analyzer. The results showed Tg shifted toward higher temperature for all type of filler compared to neat PVC. Also, thermal conductivity measurement values illustrated that PVC/bentonite composites have a good thermal insulation at 12wt%, thermal conductivity was decreased from 0.222 W/m.K for neat PVC to 0.11 W/m.K at 12wt% PVC/bentonite composites. Organoclay give the best possible water absorbability of the PVC, with other word making it moisture resistant .The higher the filler content the higher burning time, the lower rate of burning and the lower height of the flame which are evident at 12wt% for all fillers.